Efficacy of straight versus angled interdental brushes on interproximal tooth cleaning: a randomized controlled trial. Issue 2 (24th July 2013) - Jordan, RA; Hong, HM; Lucaciu, A; Zimmer, S
Abstract Background To investigate interproximal biofilm reduction with an angled interdental brush as compared to a straight interdental brush (standard control) in a clinical, single‐centre, single‐blind, controlled, parallel‐group trial. Methods Recruitment and examinations of the subjects were performed at the Witten/Herdecke University School of Dental Medicine. 128 volunteers, aged 20–65 years, were recruited and stratified according to sex and age. Two groups with 64 subjects each used either straight (standard control) or angled (test group) handgripped interdental toothbrushes of the same bristle stiffness. After a 12‐day home‐care habituation period, participants received a professional tooth cleaning followed by a 48‐h plaque regrowth period. At the intervention appointment, plaque was recorded with a fluorescent revelator and soft tissue damage was noted (T0). Interdental brushing was performed by the participant for 2 min, and clinical parameters were recorded again (T1). The primary efficacy end point was the difference in modified Proximal Plaque Index (mPPI) after brushing compared to baseline. Secondary efficacy end points were mPPI differences in subgroups (anterior vs. posterior teeth; vestibular vs. oral tooth surfaces). Safety end point was the Danser gingival abrasion index (DI). Results mPPI showed lower scores after brushing within all (sub)groups (P < 0.01). mPPI brushing efficacy (ΔT0 − T1) in subjects using straight interdental brushes was significantly higher as compared to angled interdental brushes (P < 0.0001). Straight interdental brushes were significantly more effective in posterior teeth, when used from vestibular and from oral tooth surfaces (P < 0.0001, P < 0.01 and P < 0.0001, respectively). No significant differences were found between the groups in anterior teeth and concerning soft tissue damage. Conclusions Straight interdental brushes may better remove plaque interproximally when compared to angled interdental brushes.